2017
DOI: 10.1590/0100-3984.2015.0102
|View full text |Cite
|
Sign up to set email alerts
|

Modified approach to the characterization of adrenal nodules using a standard abdominal magnetic resonance imaging protocol

Abstract: ObjectiveTo describe a modified approach to the evaluation of adrenal nodules using a standard abdominal magnetic resonance imaging protocol.Materials and MethodsOur sample comprised 149 subjects (collectively presenting with 132 adenomas and 40 nonadenomas). The adrenal signal intensity index was calculated. Lesions were grouped by pattern of enhancement (PE), according to the phase during which the wash-in peaked: arterial phase (type 1 PE); portal venous phase (type 2 PE); and interstitial phase (type 3 PE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…Conversely, in AL with no signal drop on CS, the values of wash-out parameters, both of RWO and AWO, were significantly lower, with percentage values of both RWO and AWO suggestive of non-adenomas adrenal tumors, even with the occurrence (33%) of "lipid-poor" adenomas in this group of lesions. Our results are in line with the data reported in the literature regarding the percentage values of RWO and AWO observed in different AL such as adenomas, benign, non-adenomas, and malignant adrenal tumors [13,[23][24][25][26][27]. Indeed, a previous study [13] reported that "lipidpoor" adenomas may show RWO and AWO values, both at 5 and 10 min after contrast administration, significantly lower compared to "lipid-rich" adenomas, but similar to those of non-adenoma lesions such as pheochromocytoma or malignant tumors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Conversely, in AL with no signal drop on CS, the values of wash-out parameters, both of RWO and AWO, were significantly lower, with percentage values of both RWO and AWO suggestive of non-adenomas adrenal tumors, even with the occurrence (33%) of "lipid-poor" adenomas in this group of lesions. Our results are in line with the data reported in the literature regarding the percentage values of RWO and AWO observed in different AL such as adenomas, benign, non-adenomas, and malignant adrenal tumors [13,[23][24][25][26][27]. Indeed, a previous study [13] reported that "lipidpoor" adenomas may show RWO and AWO values, both at 5 and 10 min after contrast administration, significantly lower compared to "lipid-rich" adenomas, but similar to those of non-adenoma lesions such as pheochromocytoma or malignant tumors.…”
Section: Discussionsupporting
confidence: 93%
“…These data are concordant with the results of other studies which suggested that lesion wash-out may be assessed earlier at 5 min post-contrast injection, shortening the dynamic imaging protocols both on MRI [7] and computed tomography (CT) [17][18][19]. In this regard, a modified MRI protocol using different imaging parameters has been recently proposed for the characterization of adrenal nodules [26]. On a final note, it should be highlighted that DCE quantitative parameters values showed greater ranges than ASII in our study; while we cannot provide a clear explanation to this finding, it might suggest a higher degree of variability, making ASII preferable over RWO and AWO.…”
Section: Discussionsupporting
confidence: 89%
“…However, the adrenal gland is also commonly the site of metastases and hemorrhages, as well as, to a lesser degree, primary tumors ( 16 ) . Differentiating between potentially malignant and benign lesions is essential, because metastases to the adrenal glands are common ( 17 ) , so much so that several studies are being developed in order to examine the issue ( 18 - 21 ) . Although adrenal hemorrhage is rare, its consequences are potentially fatal, especially if it is not diagnosed in a timely manner.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have highlighted the importance of MRI in the improvement of the diagnosis of abdominal and gastrointestinal diseases (13)(14)(15)(16)(17) . Patients with active inflammation identified by colonoscopy had more significant restricted diffusion, more pronounced edema, and greater wall thickening than did those with inactive disease.…”
Section: Discussionmentioning
confidence: 99%